Vamos fazer um escândalo: a trajetória da desnaturalização da violência contra a mulher e a folksonomia como ativismo em oposição a violência sexual no Brasil - Romeiro, Nathália Lima (2019)
This thesis talks about the denaturalization of sexual violence against women from the study of the folksonomy of Hashtags #primeiroassedio and #mexeucomumamexeucomtodas on social media Facebook. We base its theoretical framework on gender studies especially related to sexual violence against women. We analyzed the normative instruments that criminalized violence against women from the colonial period until 2018. We discussed the folksonomy of Hashtags in social media as a form of activism to broaden the discussion about sexual violence in these spaces. For this, we are based on studies coming from Sociology, Philosophy, Psychology and Information Science. We adopt as a general objective: to understand if the normative instruments on sexual violence and social media serve as punishment, denunciation and formation of networks support against sexual crimes suffered by girls and women. And in relation to the specific objectives: a) we base theoretically the themes that move the research universe: sexual violence, studies of gender and folksonomy; b) identify and analyze the Facebook’s manifestations of social media activism about sexual violence popularized in Hashtags #primeiroassedio and #mexeucomumamexeucomtodas; and c) We analyze the discourse of men and women in the reports collected from the Hashtags. As for the nature of the research, we classified it as quanti-qualitative because the research counts on a stage of quantitative data collection (mapping of Hashtags) that become inputs for the qualitative analysis, allowing to observe the phenomenon of militancy against sexual violence through Hashtags. The methodology of this research is characterized as bibliographic, exploratory and documentary. Regarding data collection, it was performed during the months of December 2018 and January 2019. We created categories to organize the information collected and perform the data analysis. With regard to quantitative data, we present from graphs and figures exemplifying the posts of each created category (photos, videos, reports, news and others). On the qualitative approach, we perform an analysis of the discourses present in the contents of the category "reports". With this study, we came to the conclusion that social media serve as a space for activism, outreach and formation of support networks in the struggle opposition to the violence against women. We believe that allying knowledge about the organization of knowledge and studies of social media and studies of gender are fundamental for the Science of Information as an applied social science to look at naturally digital phenomena.